Re: fullsimplify problem

*To*: mathgroup at smc.vnet.net*Subject*: [mg52943] Re: fullsimplify problem*From*: "Steve Luttrell" <steve_usenet at _removemefirst_luttrell.org.uk>*Date*: Fri, 17 Dec 2004 05:19:29 -0500 (EST)*References*: <cprjjd$r57$1@smc.vnet.net>*Sender*: owner-wri-mathgroup at wolfram.com

This looks correct to me. Your equation says that something equals minus itself, so the something must be zero. You could also try evaluating ( - a / b^2) == ( + a / b^2)//Reduce to obtain the result a\[Equal]0&&b\[NotEqual]0. Steve Luttrell "symbio" <symbio at has.com> wrote in message news:cprjjd$r57$1 at smc.vnet.net... > Given ( - a / b^2) = = ( + a / b^2), it can be written as (-2 a / b^2), > but > when I use FullSimplify on that equation, I get the incorrect result ( a / > b ) = = 0. How is this possible? > > In[2]:= > -a/b^2 == a/b^2 > % // FullSimplify > Out[2]= > \!\(\(-\(a\/b\^2\)\) == a\/b\^2\) > Out[3]= > \!\(a\/b == 0\) > > In[5]:= > -2a/b^2 == 0 // FullSimplify > Out[5]= > \!\(a\/b == 0\) >